Study on Reproductive Biology of Rhododendron longipedicellatum: A Newly Discovered and Special Threatened Plant Surviving in Limestone Habitat in Southeast Yunnan, China - Li, Taiqiang; Liu, Xiongfang; Li, Zhenghong; Ma, Hong; Wan, Youming; Liu, Xiuxian; Fu, Liyong (Frontiers in plant science, 2018)
is a narrow endemic species and a subject of urgent demand in the domestic market and overseas. Its fascinating shapes, brilliantly gilvous flowers, and unusual flowering time endow this species with extremely high ornamental value. However, only five wild populations of surviving in limestone habitat have been found through elaborate field investigation, and the number of the populations decreases further or is even confronted with risk of extinction due to the damage of human activities. To enhance the protection and utilization of , this study systematically investigated several important aspects of reproductive biology, including floral syndrome, pollen viability and stigma receptivity, petal color reflectance, breeding system, and pollination biology. The results demonstrated that arched styles not only create obvious herkogamy that avoide self-pollination, but also effectively reduce rain damage to the intrinsic characteristics of the stigma surface secretions, promoting the female fitness of in poor weather. Pollen viability maintained a high level over the flowering period. The reflectance spectrum of petals had two peaks at wavelengths of 360 and 580 nm. Tests of OCI, P/O and artificial pollination all indicated that was self-compatible and that the breeding system was mixed mating. Geitonogamy mediated by was the primary pollination route in the natural environment, which suggested that the breeding system of might be evolving from selfing to outcrossing. The pollination vector of was very specific, in that only was confirmed to deliver pollen to the stigmas. Visitation frequency was influenced by the activity rhythms and resource requirements of the different castes (i.e., sex). workers were the most effective pollinators because of higher visitation frequency and more effective contribution to fruit production, whereas the presence of males might enhance pollen flow within the population to a certain extent. Finally, these findings not only provided a reliable theoretical basis for hybridization breeding of as parents, but also laid a solid foundation for further molecular biology studies to more broadly reveal the mechanisms of its endangerment in the future.